Discurso(s) do(s) outro(s) na imagem de si: um estudo discursivo dos textos didáticos destinados à formação de formadores indígenas - Moraes, Milena Borges de (2009)
Our research aims to analyze the discursive construction of ethos in the discourse of the indigenous teacher, seeking to understand how discursive practices historically stereotyped by non-Indian determine the images, the ethos that the subject "Indian" professor constructs himself in the discourse intended for educational training indigenous trainers. We work with the hypothesis that the discourses produced by the indigenous teachers textbook for training of Indian students, the Other constituent of his speech is his pocket, his neighbor, on the contrary is non-Indian who live a conflicted relationship since that the Portuguese landed in American continent in 1500. From this perspective, we take as theoretical and methodological discourse analysis of French oriented, highly nuanced by pecheuxtianos and maingueneanos tones. The empirical corpus mobilized for this research consists of the book O índio brasileiro: o que você precisa saber sobre os povos indígenas no Brasil de hoje (The Brazilian Indian: what you need to know about indigenous peoples in Brazil today) volume 12, which includes the series Vias dos Saberes (Ways of Knowledge) Coleção Educação para Todos (Collection Education for All), written by the Indian Baniwa whose goal to provide subsidies for training of indigenous students in undergraduate courses in intercultural level. Our analysis indicates that the image of discursive enunciator / Indian is a militant and his discourse is overlapped by the discourse of the non-Indian in a relation conflicting and nomad.